2009
DOI: 10.1016/j.biopha.2009.04.045
|View full text |Cite
|
Sign up to set email alerts
|

JNK/AP-1 pathway is involved in tumor necrosis factor-α induced expression of vascular endothelial growth factor in MCF7 cells

Abstract: Vascular endothelial growth factor (VEGF) has been implicated in breast tumor angiogenesis. And tumor necrosis factor-α (TNF-α) is a positive regulator of VEGF. This study was aimed to identify the signalling pathway of TNF-α in VEGF expression regulation in breast cancer cell line MCF7. Using luciferase reporter assays, we demonstrated that TNF-α significantly increased activator protein-1 (AP-1) transcriptional activity in the MCF7 cells. The expression of the AP-1 family members c-Jun, c-Fos and JunB and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 31 publications
1
34
1
1
Order By: Relevance
“…[35][36][37] Furthermore, VEGF expression was found to be markedly increased and correlated with microvessel density in nasopharyngeal carcinoma patients. 30 Similarly, we herein found that TNFAIP2 is a downstream target of TNFa that acts as a potential angiogenic factor, as shown by the association of its expression with microvessel density in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…[35][36][37] Furthermore, VEGF expression was found to be markedly increased and correlated with microvessel density in nasopharyngeal carcinoma patients. 30 Similarly, we herein found that TNFAIP2 is a downstream target of TNFa that acts as a potential angiogenic factor, as shown by the association of its expression with microvessel density in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…Erk activation mediates VEGF gene transcription following Ras induction or growth factor stimulation (20,21). Moreover, activation of JNK and p38 following cytokine or growth factor stimulation leads to increased VEGF expression by increasing the stability of its mRNA or gene transcription (22)(23)(24)(25)(26)(27). The VEGF promoter contains several potential binding sites for transcriptional factors, including hypoxia-inducible factor-1, Sp1, AP1, and AP2 (1).…”
Section: Discussionmentioning
confidence: 99%
“…Thalidomide inhibits expression of the pro-angiogenic factors VEGF and basic fibroblast growth factor (bFGF) via mechanisms involving tumor necrosis factor-alpha (TNFalpha) [12,[30][31][32] and transcriptional activation of the VEGF promoter [33]. Tamoxifen inhibits angiogenesis and VEGF by ER-dependent [6,11] and -independent mechanisms [32].…”
Section: Discussionmentioning
confidence: 99%